Pencatatan Laporan Keuangan Sederhana pada UMKM Angkringan Istimewa dan UMKM Teh Poci di Sedayu Bantul Yogyakarta - samudra-123, guntur_; Budiantara, Martinus (Lembaga Dongan Dosen, 2024)
Based on the results of surveys and interviews conducted in Sedayu, Bantul, Yogyakarta, it was found that MSME actors do not understand the importance of financial statements. This makes it difficult for them to know their monthly profits and distinguish between business and personal finances. The purpose of this community service activity is to improve understanding and skills in the preparation of simple financial statements. The activity will be carried out in October 2024, with the population of MSME actors in the area. The sample taken consisted of Angkringan Istimewa MSMEs and Teh Poci MSMEs.Activity methods included surveys, socialization, and training. As a result, MSME actors gain new knowledge about the preparation of financial statements, which is expected to support the sustainability of their businesses.